ANTIQUORUM SENSING ACTIVITY OF ESSENTIAL OILS ISOLATED FROM DIFFERENT SPECIES OF THE GENUS PIPER - OLIVERO V., Jesús T.; PÁJARO C., Nerlis P.; STASHENKO, Elena (Vitae, 2011)
Quorum sensing is a bacterial communication mechanism that depends on population density, and occurs through molecules called autoinducers. These molecules activate receptors, enabling the transcription of genes that encode information needed to control several biochemical mechanisms associated with bacterial survival and pathogenicity. The aim of this study is to evaluate the inhibitory effect of essential oils of three species of Piper on the production of violacein, induced by N-hexanoyl homoserine lactone in Chromobacterium violaceum CV026. Results show that essential oils from Piper bredemeyeri, Piper brachypodom and Piper bogotence present 50% inhibitory concentration (IC50) for quorum sensing of 45.6 µg/mL, 93.1 µg/mL, and 513.8 µg/mL, respectively. However, in terms of cell growth, IC50 values for these oils are greater than 1000 µg/mL. These data suggest that essential oils isolated from Piper species found in Colombian flora are good candidates for the development of antiquorum sensing molecules, with possible applications in the control of bacterial diseases.